Factors Affecting The Interest Of Prospective Students In Choosing The D3- Electronics Engineering Program - Hadi, Abdul; Wahana, Desi; Fatkhurahman, Fatkhurahman (Politeknik Negeri Bengkalis, 2024)
The development of the electronics engineering study program has experienced rapid progress in variousaspects, such as microelectronics and semiconductor technology, renewable energy technology, smart grid, Internet ofThings (IoT), communication networks, automation and robotics, and artificial intelligence (AI). However, at Polbeng,prospective students' interest in choosing this study program is quite concerning. Using a survey method conduct ed onhigh school students specializing in electrical engineering in the Riau Province with a sample of 125 respondents,questionnaires were distributed online, and the data were analyzed using quantitative techniques with multiple linearregression. The results show that out of the four factors suspected to influence interest in choosing, namely: motivation(X1); talent (X2); family (X3); and society (X4), only two factors significantly influence, which are the factors ofmotivation and talent. Motivation is influenced by career prospects, campus image, choices, promotions/socialization,and the proximity of the campus to their residence. Meanwhile, talent is determined by academic performance, skillspossessed, creativity in innovation, satisfaction in the chosen department, and independence factor. These two factorsproved to be the most dominant in influencing the choice of study program.